Relationship between Knowledge and Health Conditions with Incidents to Pregnant Women in the Working Area of the Kuta Baro Aceh Besar Health Center - Desria Muliati (PT FORMOSA CENDEKIA GLOBAL, 2022)
Pregnant women who suffer from KEK events have a risk of sudden maternal death during the perinatal period or the risk of giving birth to LBW. The purpose of this study was to analyze the knowledge of pregnant women and the health conditions of pregnant women with the incidence of KEK at the Kuta Baro Aceh Besar Community Health Center in 2020. This research is analytical with a cross-sectional design. Sampling was purposive sampling with a sample size of 74 pregnant women. The data in this study were obtained from primary and secondary data using the interview method guided by the questionnaire. Analysis of the data in this study using the Chi Square test. The results showed that there was a relationship between the knowledge of pregnant women and the incidence of KEK in pregnant women with a p value of 0.034 (p <0.05) and there was a relationship between the health conditions of pregnant women and the incidence of CED in pregnant women with a p value of 0.026 (p <0.05). It can be concluded that there is arelationship between knowledge and health conditions with the incidence of KEK in pregnant women.